Encountering the book of Genesis - Arnold, Bill T. (Grand Rapids, MI Baker Books, 1998)
"The Book of Genesis stands as one of the most important books of the entire Bible, but despite the familiarity of its stories, the meaning and significance of the narratives are not always readily apparent. To help readers come to a clear understanding of this important book, Bill Arnold moves through Genesis section by section, exploring its main themes and sorting through its difficult interpretive issues. Encountering the Book of Genesis also features numerous illustrations, sidebars addressing contemporary concerns, and various study aids."--BOOK JACKET.
Encountering God's creation (Genesis 1-11) -- Encountering Abraham: God's faithful servant (Genesis 12-25) -- Encountering Jacob: God's troubled servant (Genesis 25-36) -- Encountering Joseph: God's model servant (Genesis 37-50) -- Encountering the authorship of Genesis.
Includes bibliographical references (pages 219-220) and indexes.
Keywords: Bible. -- Textbooks; Textbooks